Gender differences in substrate for endurance exercise - Tarnopolsky, L. J.; MacDougall, J. D.; Atkinson, S. A.; Tarnopolsky, M. A.; Sutton, J. R. (Journal of Applied Physiology, 1990)
The effects of gender on substrate utilization during prolonged submaximal exercise were studied in six males and six equally trained females. After 3 days on a controlled diet (so that the proportions of carbohydrate, protein, and fat were identical), subjects ran on a treadmill at a velocity requiring an O2 consumption of approximately 65% of maximal. They ran a total "distance" of 15.5 km with a range in performance time of 90-101 min. Plasma glycerol, glucose, free fatty acids, and selected hormones (catecholamines, growth hormone, insulin, and glucagon) were measured throughout and after the run by sampling from an indwelling venous catheter, and glycogen utilization was calculated from pre- and postexercise needle biopsies of vastus lateralis. Exercise protein catabolism was estimated from 24-h urinary urea nitrogen excretion over the test day and a nonexercise day. The males were found to have significantly higher respiratory exchange ratios (mean 0.94 vs. 0.87), greater muscle glycogen utilization (by 25%), and greater urea nitrogen excretion (by 30%) than the females. No gender differences were evident in the hormonal response to the exercise with the exception of a lower insulin concentration and a higher epinephrine concentration in the males. We conclude that, during moderate-intensity long-duration exercise, females demonstrate greater lipid utilization and less carbohydrate and protein metabolism than equally trained and nourished males.